2011
DOI: 10.1042/cs20100440
|View full text |Cite
|
Sign up to set email alerts
|

Decreased numbers of peripheral blood dendritic cells in patients with coronary artery disease are associated with diminished plasma Flt3 ligand levels and impaired plasmacytoid dendritic cell function

Abstract: We investigated whether activation of circulating DCs (dendritic cells) or levels of Flt3L (FMS-like tyrosine kinase 3 ligand) and GM-CSF (granulocyte/macrophage colony-stimulating factor), haematopoietic growth factors important for DC differentiation, could account for reduced blood DC numbers in CAD (coronary artery disease) patients. Concentrations of Flt3L and GM-CSF were measured in plasma from CAD patients (n = 15) and controls (n = 12). Frequency and phenotype of mDCs (myeloid dendritic cells) and pDCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 51 publications
(76 reference statements)
1
30
0
Order By: Relevance
“…Other researchers detected decreased numbers of pDCs in patients with troponin-positive unstable coronary artery syndromes (Van Vré et al, 2006), end-stage heart disease (Athanassopoulos et al, 2004), and advanced CAD (Yilmaz et al, 2009; Van Vré et al, 2010). Furthermore, an inverse correlation between the severity of CAD and pDC numbers was observed (Yilmaz et al, 2009; Van Brussel et al, 2011). Decrease in pDC levels observed in acute coronary events could reflect increased recruitment of pDCs in supporting advanced pronflammatory responses preceding the acute cardiovascular event (Sorrentino et al, 2010).…”
Section: Proinflammatory Activities Of Pdcs In Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers detected decreased numbers of pDCs in patients with troponin-positive unstable coronary artery syndromes (Van Vré et al, 2006), end-stage heart disease (Athanassopoulos et al, 2004), and advanced CAD (Yilmaz et al, 2009; Van Vré et al, 2010). Furthermore, an inverse correlation between the severity of CAD and pDC numbers was observed (Yilmaz et al, 2009; Van Brussel et al, 2011). Decrease in pDC levels observed in acute coronary events could reflect increased recruitment of pDCs in supporting advanced pronflammatory responses preceding the acute cardiovascular event (Sorrentino et al, 2010).…”
Section: Proinflammatory Activities Of Pdcs In Atherosclerosismentioning
confidence: 99%
“…Plaque tissues of patients with ischemic complications (and shoulder regions especially) expressed higher levels of CD83 (Siglec), a marker of DC activation (Erbel et al, 2007). However, Van Brussel et al (2011) showed that pDCs derived from CAD patients expressed lower levels of CD83 and TLR7 and as a consequence produced less IFN-α. Similarly, decreased expression of proinflammatory cytokines (IL-1β and IL-6) was observed in type 2 diabetic patients with atherosclerotic complications (Corrales et al, 2007).…”
Section: Proinflammatory Activities Of Pdcs In Atherosclerosismentioning
confidence: 99%
“…As DC precursors they are relatively immature and express only low levels of adhesion and costimulatory molecules—at least in physiological conditions [10–12]. mDCs (0.26% among leukocytes) descend from the myeloid lineage, and express blood DC antigen (BDCA)-1 (= CD1c), CD11c, and Toll-like receptors TLR2, TLR4, TLR5, and TLR3 [1315].…”
Section: Circulating Dcs In Cadmentioning
confidence: 99%
“…38 Although these studies have failed to unequivocally identify certain DC subsets as biomarkers of disease, the majority of studies observed a decline in DC numbers in CAD. With a finer delineation of circulating DC subsets/precursors, including CD141…”
Section: Cd11cmentioning
confidence: 99%